Development of phytotoxicity indexes and their correlation with ecotoxicological, stability and physicochemical parameters during passive composting of poultry manure. (August 2016) - Young, Brian Jonathan; Rizzo, Pedro Federico; Riera, Nicolás Iván; Torre, Virginia Della; López, Valeria Alejandra; Molina, Cecilia Denisse; Fernández, Florencia Estefanía; Crespo, Diana Cristina; Barrena, Raquel; Komilis, Dimitrios; Sánchez, Antoni
Highlights: Two new phytotoxicity indexes were proposed for use during compost quality assessment. Using PCA, two groups of parameters associated to each sampling time (start, end) were detected. A positive correlation between ecotoxicological parameters and biological activity was found. Abstract: Both raw and composted poultry manure is applied as soil amendment. The aims of this study were: (1) to develop phytotoxicity indexes for organic wastes and composts, and (2) to assess the correlation among phytotoxicity indexes, ecotoxicological endpoints and stability and physicochemical parameters during passive composting of poultry manure. Six 2-m 3 composting piles were constructed and four parameter groups (physicochemical and microbiological parameters, ecotoxicological endpoints, and biological activity) were determined at four sampling times during 92 days. Extracts were used to carry out acute toxicity tests on Daphnia magna, Lactuca sativa and Raphanus sativus . Composting decreased average toxicity 22.8% for the 3 species and D. magna was the most sensitive species. The static respiration index decreased from 1.12 to 0.46 mg O2 g OM h −1 whilst organic matter reduced by 64.1% at the end of the process. Escherichia coli colonies remained higher than values recommended by international guidelines. The D. magna immobilization test allowed the assessment of possible leachate or run-off toxicity. The new phytotoxicity indexes (RGIC0.8 and GIC80% ), proposed in this study, as well as salinity, proved to be good maturity indicators. Hence, these phytotoxicity indexes could be implemented in monitoring strategies as useful ecotoxicological tools. Multivariate analyses demonstrated positive correlations between ecotoxicological endpoints (low toxicity) and biological activity (stability). These two parameter groups were associated at the final sampling time and showed negative correlations with several physicochemical parameters (organic and inorganic contents). The final poultry manure compost was rendered stable, but immature and, thus, unsuitable for soil amending.